A CYP380C10 gene is required for waterproofing and water retention in the insect integument. (April 2022) - Wang, Zhe-Chao; Peng, Lu-Yao; Cheng, Xu; Yang, Rui-Rui; Li, Dan-Ting; Zhang, Chuan-Xi; Bao, Yan-Yuan
Graphical abstract: Highlights: CYP380C10 is the ancestor gene of the CYP4G subfamily in N. lugens . CYP380C10 is involved in CHC biosynthesis. Knockdown of CYP380C10 generated lethal defect. Knockdown of CYP380C10 decreased the bodyweight and the amounts of CHCs. CYP380C10 is an importantly functional gene in waterproof and water-retention. Abstract: Cuticular hydrocarbons (CHCs) are important components in the integument of insects and are required for development and survival. Insect-specific CYP4G subfamily, of the P450 enzymes, catalyze the oxidative decarbonylation step in the biosynthesis of CHCs. Here, we characterized CYP380C10 gene function in a Hemiptera rice pest, Nilaparvata lugens . We used RNA interference–mediated expression silencing to reveal that NlCYP380C10 played a key role in waterproofing and water–retention in the integument of N. lugens . Knockdown of NlCYP380C10 significantly reduced body weight and caused mortality. Scanning electron microscopy showed the loss of the lipid layer on the surface of the abdominal cuticle of the ds NlCYP380C10 -injected adults. Furthermore, CHC profile analysis revealed that NlCYP380C10 knockdown significantly decreased the amounts of CHCs in adult females. This suggested that NlCYP380C10 was involved in CHC biosynthesis. Reduction of CHC content caused the loss of the intact lipid layer of the cuticle, which resulted in loss of the waterproofing and water-retention functions. This led to failure of molting and eclosion. Our findings expanded the knowledge of CHC biosynthesis in the insect integument and led to a better understanding of the functional roles of CYP450 genes involved in waterproofing and water–retention in insects.